Evangelicals, catholics, and Vodouyizan in Haiti: the challenges to living together - Joseph, Celucien L.; Clorméus, Lewis Ampidu (Bloomsbury Academic, 2024)
"Explores the antagonistic history of Haiti's two dominant religious traditions - Christianity and Vodou - an antipathy which has had a marked impact on nation-building in Haiti, weakening Haitian democracy and challenging the widespread acceptance of religious freedom and expression. Using different theoretical frameworks and epistemological traditions, this volume examines the misunderstandings between the two faiths and provides a manifesto for building constructive channels towards mutual cooperation and peace"--